Angus Graham and the Scottish harbours - Shotton, Elizabeth (Proceedings of the Society of Antiquaries of Scotland, 2024)
The Scottish antiquarian Angus Graham (1892–1979) had a distinguished career with the Royal Commission on the Ancient and Historical Monuments of Scotland and service with the Society of Antiquaries of Scotland. These roles, in addition to his prolific publications in both the Proceedings of the Society of Antiquaries of Scotland (PSAS) and regional journals on a broad range of subjects, firmly established his position in the history of Scottish archaeological and antiquarian studies. It is Graham’s research on Scotland’s harbours and havens, primarily undertaken after his retirement in 1957, that is of particular interest here, given the scale of its ambition and manner of its execution. Encompassing the entire coastline of the Scottish mainland, 536 sites were investigated by Graham from 1961 to shortly before his death, with two final papers in the sequence published posthumously, the last assembled by his long-time collaborator and niece Joanna Gordon. Graham’s work was the first comprehensive inventory of landing sites, piers and quays in the UK or Ireland, serving to establish the extent and diversity of these structures that are so critical to understanding the cultural and economic history of a region. Graham’s extensive research on harbours acknowledged the urgent need to document this increasingly redundant and vulnerable coastal infrastructure long before the increased threat to coastal heritage due to climate change was recognised in the diverse disciplines currently studying harbours and landing sites. Given the uneven landscape of harbour research in the recent past, Graham’s contribution not only represents work of a scope that has rarely been matched but has a coherence in its structure, undoubtably drawn from his long tenure with the RCAHMS, that offers a baseline and template for the inventories of maritime structures that are so urgently needed.